Modifying supersaturation rate with membrane area to volume ratio: scaling reduction and improved crystal growth control in membrane distillation crystallisation - Ouda, Alaa Samir; Bajón Fernández, Yadira; McAdam, Ewan (Elsevier, 2023)
This study provides detailed characterisation of nucleation kinetics, induction time and supersaturation to understand scaling and crystal growth in membrane distillation crystallisation. Membrane area was used to moderate supersaturation rate, as a method to transition across the metastable zone without modifying boundary layer conditions. Increasing membrane area sustained the same water vapour flux but increased supersaturation rate within the crystallising solution (sodium chloride). This reduced induction time and increased the supersaturation level at induction. Membrane scaling was minimised by increasing supersaturation rate despite an increase in nucleation rate. This conforms with classical nucleation theory but contradicts membrane distillation crystallisation literature, where elevated supersaturation is often linked to advanced scaling. The transition from heterogeneous to homogeneous nucleation was evidenced once greater supersaturation at induction was achieved. The probability for scaling within the low supersaturation domain was confirmed through diagnostic investigation of the scaling deposit formed, and the growth mechanism within the scaling layer related to the relevant supersaturation region. Crystal size and morphology were also related to the metastable region, where membrane-to-volume ratio can facilitate higher nucleation rates complemented by greater crystal growth. This study provides critical insight for the development of scaling mitigation strategies and creates a basis for the sustainable design of thermal membrane crystallisation systems.
Keywords: Scaling mitigation; Zero liquid discharge; Brine; Direct contact; Hollow fibre; NaCl